An accessory prefrontal cortex–thalamus circuit sculpts maternal behavior in virgin female mice. (7th November 2022) - Glat, Micaela; Gundacker, Anna; Cuenca Rico, Laura; Czuczu, Barbara; Ben‐Simon, Yoav; Harkany, Tibor; Pollak, Daniela D
Abstract: The ability to care for the young is innate and readily displayed by postpartum females after delivery to ensure offspring survival. Upon pup exposure, rodent virgin (nulliparous) females also develop parental behavior that over time becomes displayed at levels equivalent to parenting mothers. Although maternal behavior in postpartum females and the associated neurocircuits are well characterized, the neural mechanisms underlying the acquisition of maternal behavior without prior experience remain poorly understood. Here, we show that the development of maternal care behavior in response to first‐time pup exposure in virgin females is initiated by the activation of the anterior cingulate cortex (ACC). ACC activity is dependent on feedback excitation by Vglut2 + /Galanin + neurons of the centrolateral nucleus of the thalamus (CL), with their activity sufficient to display parenting behaviors. Accordingly, acute bidirectional chemogenetic manipulation of neuronal activity in the ACC facilitates or impairs the attainment of maternal behavior, exclusively in virgin females. These results reveal an ACC‐CL neurocircuit as an accessory loop in virgin females for the initiation of maternal care upon first‐time exposure to pups. Synopsis: The neural mechanisms underlying the acquisition of parental behavior in rodent virgin females are poorly characterized. Here, first‐time pup exposure is shown to induce a feedback excitation loop between the anterior cingulate cortex (ACC) and the centrolateral nucleus of the thalamus (CL) to initiate parenting behavior in virgin female mice. Pup exposure initiates the development of maternal care behavior in virgin female mice by activation of the ACC. The ACC controls the display of parenting behavior through feedback excitation with galanin + neurons of the CL. The ACC‐CL neurocircuit constitutes an accessory loop to the core circuit of maternal care to induce parenting behavior in virgin females. Abstract : The development of maternal care behavior in response to first‐time pup exposure in virgin female mice is initiated by the activation of the anterior cingulate cortex.